Wissenschaftliches Arbeiten - Bänsch, Axel 1941-; Alewell, Dorothea 1964- (De Gruyter Oldenbourg, 2020)
The textbook offers detailed advice and rules for each step in developing a scientific research project. It also describes typical assessment criteria and the rules of good scientific practice. New features in the current edition include suggestions for conducting research using modern media, particularly online and with databases, and for documenting the results in literature management programs
Keywords: Abschlussarbeit; Bachelor/Master thesis; Bachelorarbeit; Gute wissenschaftliche Praxis; Masterarbeit; Plagiat; Seminararbeit; Term paper; Wissenschaftliches Schreiben; citation; writing; BUSINESS & ECONOMICS / General; Wissenschaftliches Arbeiten; Wissenschaftliches Manuskript; Studium; Betriebswirtschaftslehre